Quality Assurance Statement of Companies Listed on the Indonesia Stock Exchange 2021 - Susilo, Lilianda; Meiden, Carmel (AIBPM Publisher, 2023)
This research was conducted to analyze quality assurance statement contained in the sustainability report. Sustainability reports that also issue assurance statements are still voluntary, assurance statements are intended to increase the accuracy and credibility of the sustainability report. The method used is content analysis method quantitatively and qualitatively. The objects used are 25 companies registered on the Indonesia Stock Exchange in 2021, where 11 companies use the ISAE 3000 proxy and 14 companies use the AA1000AS proxy which is divided into 7 business sectors and 8 assurance providers. From this study it was found that the assurance statements included in the sustainability reports of several companies in Indonesia are of high quality and the assurance statements issued by KAPs and non-KAPs have a high percentage for 2021. Assurance statements based on each industry sub- sector and assurance providers have a high presentation. Based on the quantitative and qualitative methods, there were several contents that were 100% fulfilled by the 25 companies, namely the contents of the title, addressee, name of the assuror, date of report, and location of the assuror. Keywords: sustainability report, assurance statement, quality assurance